IMPROVING THE TREATMENT OF VIRAL STOMATITIS IN CHILDREN DURING ENTERIC VIRAL INFECTIONS - Inomjon N. Akhmadov (Central Asian Journal of Medicine, 2024)
In children, diseases of the oral mucosa caused by viral infections in the intestine occupy a special place in terms of prevalence, complexity in diagnosis and treatment. Scientific sources and studies over the past twenty years have noted that diseases of the oral mucosa caused by viral infections in the intestine are observed in up to 42%, and in various syndromes - up to 30% of these diseases. At the same time, the predominance of viral stomatitis among diseases of the oral mucosa caused by viral infections in the intestines in children, as well as the observation of 48.2% to 55.1% indicate a high prevalence of pathology. This situation is explained by the fact that the initial stages of diseases are accompanied by a lack of sufficient data on changes in both clinical and laboratory parameters, as well as the lack of a unified etiopathogenetic point of view among specialists. This indicates the need to improve the treatment and prevention of this problem.